Gender Bias in Bangladeshi School Textbooks: Not Just a Matter of Politics or Growing Influence of Islamists - Asadullah, Mohammad Niaz (The review of faith & international affairs, 2018)
In this essay, we critically reflect on the ongoing controversy over Islamization of textbooks by a secular government in Bangladesh. Based on a review of the emerging evidence on gender stereotypes in textbook contents, we argue that gender bias was widespread in government-recognized textbooks long before radical Islamic groups publicly demanded changes to the secular school curriculum. All Bangladeshi school textbooks continue to suffer from a pro-male bias regardless of whether they are based on a secular or religious curriculum. Nonetheless, Bangladesh's experience suggests that politicization of the debate on what children should learn in school can make future reforms much harder to achieve.